Holistic Development of Novice Educators: Insights from the Seven Habits of Highly Effective People - Fakhar-Ul-Zaman; Professor and Dean Faculty of Education, International Islamic University, Islamabad, Prof. Dr. Muhammad Sarwar; International Islamic University, Islamabad, Dr Muhammad Sher Baz Ali (PJE, 2024)
The present paper investigates the implementation of Stephen R. Covey’s “The 7 Habits of Highly Effective People” framework with respect to the comprehensive development of novice educators. Although the literature related to teacher preparation is large, it lacks research on the holistic development of novice educators. This paper fills this gap by analyzing how Covey’s principles correlate with the needs of novice educators and contribute to their development as successful teachers. The research problem is the search for the most effective practices and strategies to incorporate Covey’s principles in the training and professional development programs of novice educators. Based on the usage of qualitative techniques, including thematic and content analysis, this paper explores the feasibility of the implementation of the Covey’s framework throughout multiple educational settings. Overall, findings indicate that Covey’s habits of high efficiency, proactivity, prioritization, collaboration, and the desire for self-improvement are beneficial for theteaching staff and help in the comprehensive development of novice educators. The author reflects on the potential uses of the study and finds that teacher training courses should include training in the skills and qualifications gained from the habits described in Covey’s book. Also, researchers are advised to choose other areas of investigation for training specialists in various fields to ensure thorough professional development of all workers.